Trichological disorders in organ transplant recipients (OTRs): a literature review - Pasierbska, Ewa; Dębska-Ślizień, Alicja; Imko-Walczuk, Beata (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2025)
Kidney transplantation has become the preferred treatment for end-stage renal disease, significantly enhancing quality of life and life expectancy compared to dialysis. However, immunosuppressive therapy post-transplantation causes various side-effects, including skin and hair disorders. While the literature extensively documents cutaneous malignancies post-transplantation, hair disorders remain less explored. This review synthesizes the existing literature on trichological problems in transplant recipients, focusing on the correlation between immunosuppressive medications and hair disorders. A more concise version might be: The review highlights a discrepancy between patient-reported alopecia rates and physician perceptions, suggesting an underestimation of the issue. It underscores the importance of recognizing and managing trichological complications, which can significantly impact patients’ quality of life, especially in some groups such as women experiencing alopecia and in teenagers of both sexes. Further research is needed to better understand the prevalence, patterns, and mechanisms of trichological complications post-transplantation as well as to explore potential therapeutic interventions. Future studies on the etiopathogenesis of these complications can improve patient care and management strategies.